Melatonin alters bovine uterine artery hemodynamics, vaginal temperatures, and fetal morphometrics during late gestational nutrient restriction in a season-dependent manner. (13th August 2021) - Contreras-Correa, Zully E; Messman, Riley D; Sidelinger, Darcie R; Heath King, E; Sánchez-Rodríguez, Héctor L; Burnett, Derris D; Lemley, Caleb O
Abstract: The objectives were to examine melatonin-mediated changes in temporal uterine blood flow (UBF ), vaginal temperatures (VT s), and fetal morphometrics in 54 commercial Brangus heifers (Fall, n = 29; Summer, n = 25) during compromised pregnancy. At day 160 of gestation, heifers were assigned to one of the four treatments consisting of adequately fed (ADQ-CON ; 100% National Research Council [NRC ]; n = 13), global nutrient restricted (RES-CON ; 60% NRC; n =13), and ADQ or RES supplemented with 20 mg/d of melatonin (ADQ-MEL, n = 13; RES-MEL, n = 15). In the morning (0500 hours; AM ) and afternoon (1300 hours; PM ) of day 220 of gestation, UBF was determined via Doppler ultrasonography, while temperature data loggers attached to progesterone-free controlled internal drug releases were used to record VTs. At day 240 of gestation, heifers underwent cesarean sections for fetal removal and morphometrics determination. The UBF and VT data were analyzed using repeated measures of analysis of variance (ANOVA), while the morphometrics was analyzed using the MIXED procedure of SAS. Seasons were analyzed separately. In Fall, a nutrition by treatment interaction was observed, where the RES-CON heifers exhibited reduced total UBF compared with ADQ-CON (5.67 ± 0.68 vs. 7.97 ± 0.54 L/min; P = 0.039). In Summer, MEL heifers exhibited increased total UBF compared with the CON counterparts (8.16 ± 0.73 vs. 6.00 ± 0.70 L/min; P = 0.048). Moreover, there was a nutrition by treatment by time interaction in VT for Fall and Summer heifers ( P ≤ 0.005). In Fall, all groups had decreased VT in the morning compared with the afternoon ( P < 0.05). Whereas, in Summer, VT increased for ADQ-CON and RES-CON ( P < 0.0001) from morning to afternoon, the ADQ-MEL and RES-MEL remained constant throughout the day ( P = 0.648). Furthermore, the RES-MEL-PM exhibited decreased VT compared with ADQ-CON-PM (38.91 ± 0.09 vs. 39.26 ± 0.09 °C; P = 0.018). Lastly, in Fall, a main effect of nutrition was observed on fetal weights, where the RES dams had fetuses with decreased body weight when compared with ADQ (24.08 ± 0.62 vs. 26.57 ± 0.64 kg; P = 0.0087). In Summer, a nutrition by treatment interaction was observed on fetal weights where the RES-CON dams had fetuses with reduced weight when compared with ADQ-CON and RES-MEL ( P < 0.05). In summary, nutrient restriction decreased UBF and melatonin supplementation increased UBF depending on the season. Additionally, melatonin appeared to decrease VT and rescue fetal weights when supplemented in the Summer.